GENTRIFICATION OF THE CONDESA, MEXICO CITY. CONTRIBUTION FOR A DISCUSSION FROM LATIN AMERICA - Salinas-Arreortua, Luis Alberto (2014)
Tçhe La Condesa neighborhood of downtown Mexico City has undergone numerous changes in land use from residential to commercial and office, as well as demographic shifts, resulting in a noticeable transformation of the neighborhood’s landscape. All these features can be defined under the concept known as gentrification. This case study provides elements to discuss the characteristics of the process of gentrification from a Latin American perspective.